The Effect of One-Way System Implementation on Traffic Performance on Arif Rahman Hakim Road, Depok City, Indonesia - Edy Galahta Ginting, Winston; Widyaningsih, Nunung (ASTONJADRO, 2022)
Depok City has traffic movement characteristics that are no different from other cities. Traffic movements in Depok City are quite busy and even tend to be congested at certain hours, such as when people go to work and return from work as happened on Arif Rahman Hakim Road which is a 4/2D road type (4 lanes 2 divided directions) which often experiences traffic jams. Efforts to overcome traffic jams are by implementing a system change from 4/2 to 2/1 (two lanes one way) which is expected to improve traffic performance. Observing this phenomenon, this study intends to determine the effect of implementing a one-way system on traffic performance. The findings in the field show that the application of a one-way system can improve traffic performance with an increase in the level of road service in one lane. The results of multiple regression analysis using vehicle situation, side barriers, and road situations simultaneously have a significant effect on traffic performance with an effect value of 10.3%.